Zasada „zanieczyszczający płaci” a odpowiedzialność za zanieczyszczenie gleby spowodowane działalnością rolniczą (zagadnienia wybrane) - Kuraś, Bartosz (Wydawnictwo Naukowe UAM, 2012)
The subject of the paper is the „polluter pays‟ principle and certain regulations that implement that principle and provide for the liability for polluting soils as a result of agricultural activity. The objective of the paper was to assess the extent of the application of the polluter pays principle in Poland. The author concludes that the Law on the prevention of damages provides for the enforcement of the polluter pays principle, although that principle is not an absolute one. Overriding it with another, that is the „society pays‟ principle may be well founded and in line with the targets of the national agricultural policy. Such restrictions, however, must be specifically justified, and in the case of agricultural activity proper justification seems much easier to find than for industrial activities.

Le considerazioni hanno per oggetto il principio “chi inquina paga” e alcune regolazioni giuridiche scelte che attuano questo principio, ma riguardano la responsabilità per l‟inquinamento del suolo causato dalle attività agricole. L‟obiettivo dell‟articolo è di valutare in quale misura il principio “chi inquina paga” trova l‟applicazione nella responsabilità per l‟inquinamento del suolo causato da tali attività. Secondo l‟autore, la legge sulla prevenzione dei danni attua il principio “chi inquina paga”, il quale non costituisce certamente un principio assoluto. Le sue restrizioni a favore del principio “la società paga” possono trovare una giustificazione ed essere coerenti con gli obiettivi della politica agricola dello Stato. Tali restrizioni, tuttavia, richiedono una speciale motivazione. L‟attività agricola è un‟attività nei confronti della quale tale motivazione è più facile da trovare che nel caso delle attività industriali.